ANALISIS STRATEGI PEMASARAN PADA PENINGKATAN PENDAPATAN BRAND TARIU CLOTHING PONTIANAK - Sriwahyuni Sriwahyuni; Aminuyati Aminuyati; Okiana Okiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the marketing strategy to increase income of the TariuClothing Brand in Pontianak. The research method used is descriptive research with aqualitative research form. The data source of this research uses financial data from2019 to 2020 and 3 respondents who are taken include the Owner, Marketing Staffand Financial Staff of the Tariu Clothing Brand. The results of this study indicate thatthe analysis of marketing strategies on increasing income of the Tariu Clothing Brandrefers to the online sales media, there is an increase in income in January - June 2020amounting to Rp. 171. 077,000, while in offline sales the increase occurred in January- June 2019 amounting to Rp. 204,800,000.Keywords : marketing strategy and increasing revenue